Financial Status of Small Farmer Cooperative Limited (SFCL) in Surkhet District of Nepal - Tiwari, Liladhar (Journal of Advanced Academic Research, 2017)
The present study has studied the status of Small Farmers Cooperative Limited (SFCL) in Surkhet District of Nepal. The cooperative movement originated from the philosophy of cooperation and later developed as a powerful tool to support to improve socio-economic status of resource poor, vulnerable, members of the lower cast people, women, labors and peasants. The Small Farmers Cooperative Limited functions with the guiding philosophy of group principle, self-help development and institutionalization of networks at the grassroots level to reduce the poverty. SFCL has three tier structures - village level groups, inter-groups and the main committee. This study applied a descriptive and analytical research design in the specific area. Study is based on both primary and secondary sources of data. The primary data are collected through observation and questionnaires and secondary data are collected from District Cooperative Office Surkhet (DCOS), Department of Cooperative (DoC), Central Bureau of Statistics (CBS), National Planning Commission (NPC), National Cooperative Federation of Nepal (NCF/N and so on. Some of the most remarkable contributions of these institutions are: saving collection, credit investment and socio-economic improvement. The SFCLs are guided by democratic norms and shares are issued to the members who are empowered with one member one vote for the general assembly purpose. The institutions function for socio-economic development with the strong policy of being apolitical and unbiased with no discrimination of any kind on religion and gender basis. The socio-economic status of cooperative members is changed through income generation. Similarly, in the comparison of expenditure increment before and after membership, an average expense is increased, result is highly significant.